2009
DOI: 10.1186/ar2616
|View full text |Cite
|
Sign up to set email alerts
|

The proliferative human monocyte subpopulation contains osteoclast precursors

Abstract: Introduction Immediate precursors of bone-resorbing osteoclasts are cells of the monocyte/macrophage lineage. Particularly during clinical conditions showing bone loss, it would appear that osteoclast precursors are mobilized from bone marrow into the circulation prior to entering tissues undergoing such loss. The observed heterogeneity of peripheral blood monocytes has led to the notion that different monocyte subpopulations may have special or restricted functions, including as osteoclast precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 46 publications
7
44
0
1
Order By: Relevance
“…3]). These results were similar for several donors and in agreement with recent findings suggesting that a small subset of human blood monocytes may be osteoclast precursors with proliferative properties (14,24,55). In addition, we confirmed that immature (day 4) and LPSmatured MDDCs (day 8) resided in the G 0 phase of the cell cycle (Fig.…”
Section: Genetic Modification Of Immature Mddcs Is Greatly Enhanced Usupporting
confidence: 93%
“…3]). These results were similar for several donors and in agreement with recent findings suggesting that a small subset of human blood monocytes may be osteoclast precursors with proliferative properties (14,24,55). In addition, we confirmed that immature (day 4) and LPSmatured MDDCs (day 8) resided in the G 0 phase of the cell cycle (Fig.…”
Section: Genetic Modification Of Immature Mddcs Is Greatly Enhanced Usupporting
confidence: 93%
“…Inflammatory arthritides comprise a heterogeneous group of joint disorders that are characterized by chronic inflammation, and intra-articular and generalized bone loss due to deregulated bone homeostasis: bone resorption by osteoclasts (OCs) and bone formation by osteoblasts [1]. Erosions of periarticular bone are the central feature of rheumatoid arthritis (RA) and also occur in spondyloarthritis (SpA) and the erosive form of osteoarthritis [2].…”
Section: Introductionmentioning
confidence: 99%
“…OCs are multinuclear cells derived from mononuclear osteoclast progenitors (OCPs) of the monocyte-macrophage lineage, which can be matured in vitro in the presence of macrophage colonystimulating factor (M-CSF) and receptor activator of nuclear factor-κΒ ligand (RANKL) [1,3]. OCPs are found in the peripheral blood (PB) and synovial tissue of patients with RA and SpA [4], mediating bone loss locally, in the form of bone erosions and joint osteolysis, and systemically, with the loss of bone mineral density (BMD) [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, CD16 -cells also accumulate in RA synovium, and differ from CD16 + cells by their expression of 8 CD51/61, which is important for committed OCP migration and associated with osteoclast maturation [46,47]. Described results indicate that CD14 + CD16 + monocytes represent a more mature (mostly quiescent) stage in osteoclast differentiation sequence compared with CD14 + CD16 -and CD14 + CD16 int subsets [57,58] Although the cell-surface phenotype of peripheral OCPs has been extensively studied in arthritis, the functional relations of circulating OCPs to bone marrow OCPs and their bone-directed homing, mostly governed by chemokine signals, have not been clearly established. CXCR4, unique CXCL12 receptor, is highly expressed in human OCPs and mature osteoclasts, indicating that CXCL12 may be important for chemotaxis, differentiation and survival of human osteoclast lineage cells [60].…”
Section: Human Osteoclast Progenitorsmentioning
confidence: 95%
“…In physiological conditions, OCPs have been found among CD14 + CD16 -monocyte pool, possibly within the subset of immature (proliferating) monocytes (defined as CD14 + CD16 -CD64 + CD33 + CD13 lo CD115 + ) [58]. Komano et al described a highly osteoclastogenic subpopulation of peripheral blood monocytes, expressing the CD14 + CD16 -(CD33 hi )CD115 lo phenotype [46].…”
Section: Human Osteoclast Progenitorsmentioning
confidence: 99%